Modeling inter-regional patient mobility: Does distance go far enough? - Michael Irlacher; Dieter Pennerstorfer; Anna-Theresa Renner; Florian Unger (Johannes Kepler University of Linz, Department of Economics, 2021)
This paper estimates a theory-guided gravity equation of regional patient flows. In our model, a patient's choice to consult a physician in a particular region depends on a measure of spatial accessibility that accounts for the exact locations of both patients and physicians. Introducing this concept in a spatial economics model, we derive an augmented gravity-type equation and show that our measure of accessibility performs better in explaining patient flows than bilateral distance. We conduct a rich set of counterfactual simulations, illustrating that the effects of physicians' market exits on patient mobility crucially depend on their exact locations.
Additional information: A previous version of this paper was published by Renner and Pennerstorfer in 2020 as a JKU Working Paper (No. 2004).
Keywords: R10; R12; R23; I11; I18; 330; gravity model; patient mobility; spatial accessibility; two-step floating catchmentareas (2SFCA)